Analyzing Electricity Demand in Colombia: A Functional Time Series Approach - Marin, Jorge Barrientos; Marulanda, Laura Marquez; Duque, Fernando Villada (International Journal of Energy Economics and Policy, 2023)
In this work we are interested in analyzing the energy demand in Colombia for a short-term horizon, from a functional data approach. First, we make an exhaustive review of the literature on functional spaces as a potential source of statistical information. It is, of course, a theoretical reinterpretation since in practice the data are elements of a finite-dimensional space; however, very high-frequency data, properly treated, can be viewed as elements of a space of continuous functions. Second, we put such a reinterpretation into practice, by performing a spline-type smoothing of commercial energy demand, based on hourly-daily data. As a result, a function or smooth curve is obtained for each day. Finally, we expose the usefulness of this new approach for statistical analysis, modeling, and projection (or forecasting) of stochastic processes that generate high-frequency random variables.